Exploring Successful Breastfeeding Behaviors Among Women Who Have High Body Mass Indices. (February 2023) - O'Reilly, Sharleen L.; Conway, Marie C.; O'Brien, Eileen C.; Molloy, Eva; Walker, Hannah; O'Carroll, Eimear; McAuliffe, Fionnuala M.
Background: Women with high body mass indices are at risk of lower breastfeeding rates but the drivers of successful breastfeeding in this population are unclear. Research Aim: We aimed to (a) explore the barriers and enablers to breastfeeding among women with high body mass indices and (b) map specific behaviors suitable for intervention across the antenatal to postpartum periods. Methods: This was a prospective, cross-sectional qualitative study. We conducted semi-structured interviews with women with high body mass indices who successfully breastfed for 6 months or more ( n =20), partners ( n = 22), and healthcare professionals ( n =19) in Ireland during 2018. Interviews were audio recorded, and transcribed verbatim. Data were inductively coded using reflexive thematic analysis and deductively mapped within the Capability, Opportunity, Motivation–Behavior model. Results: The three themes developed were knowledge, support, and self-efficacy. Knowledge supported a participant's psychological and physical capability to engage in breastfeeding. Support was related to the social and physical opportunity to enable performance of breastfeeding behaviors. Self-efficacy influenced reflective and automatic motivation to perform breastfeeding behaviors. A multifactorial intervention design is needed to support successful breastfeeding. Conclusion: The barriers and enablers identified for participants with high body mass indices were similar to those for the broader population; however, the physicality and associated social bias of high body mass indices mean that additional support is warranted. Antenatal and postpartum breastfeeding services need a multifaceted, inclusive, and high-quality program to provide the necessary support to women with higher body mass indices.